REDUKCIONA KLITOROPLASTIKA KOD KONGENITALNE ADRENALNE HIPERPLAZIJE: NAŠA ISKUSTVA - Stojanovic, Borko; Bizic, Marta; Bencic, Marko; Djordjevic, Miroslav (Medical Research, 2025)
Introduction: Feminizing genitoplasty for congenital adrenal hyperplasia (CAH) includes clitoroplasty, vaginoplasty, urethroplasty and labioplasty. The aim is to achieve normal female anatomy without compromising sexual function. We present our technique and outcomes of reduction clitoroplasty.Methods: A total of 21 patients with CAH, aged from 13 months to 24 years (mean 22 months), underwent feminizing genital reconstruction in our center between January 2011 and December 2020. Surgical treatment included reduction clitoroplasty and labioplasty, with or without urethroplasty and vaginoplasty. Clitoroplasty was performed by complete disassembly of the clitoris into glans with neurovascular bundle and cavernosal bodies. Urethral plate was mobilized with Bucks fascia, and neurovascular bundle was dissected under Bucks fascia to preserve its’ structures. Glans cap was separated from the tips of the cavernosal bodies, avoiding injury of the arteries that run lateroventrally. Cavernosal bodies were completely removed, followed by glans reconstruction and reassembly of all entities, to attain normal clitoral morphology.Results: Follow-up ranged from 44 to 162 months (mean 84 months). An excellent aesthetic outcome with normal appearance of the genitalia was achieved in all cases. Five patients (24%) reached puberty, and all have regular menstrual cycle. Sensitivity of the reduced clitoris seemed preserved, but complete assessment was impossible due to the patients’ age.Conclusion: Reduction clitoroplasty by clitoral disassembly presents a good choice for clitoromegaly repair in patients with CAH. This approach leaves the neurovascular bundle intact and completely preserves the glans cap and urethral plate blood supply. Long-term follow-up is necessary for evaluation of sensation and sexual function.
Keywords: Congenital adrenal hyperplasia; Feminizing genitoplasty; Clitoroplasty